The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1089/tmj.2017.0035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a French Regional Telemedicine Network Dedicated to Neurological Emergencies: A 14-Year Study

Abstract: Telemedicine networks facilitate acute-phase neurological assessment and prevent unnecessary secondary interhospital transfers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Telemedicine ET was most accessible in the medical residency program, primarily in specialties where telemedicine activity was well developed in France. 12 Respondents in the survey stated emergency medicine, dermatology, geriatrics, neurology and radiology as specialties with telemedicine training in residency. These results were similar to studies published in recent years in the US, including the survey conducted at the Thomas Jefferson University, where 70% of respondents stated integrated telemedicine training in the emergency medicine hospital rotation was valuable to their curriculum, 13 and a national survey of dermatology residents conducted to assess the exposure to teledermatology training and practice indicating the need to expand teledermatology training programs.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine ET was most accessible in the medical residency program, primarily in specialties where telemedicine activity was well developed in France. 12 Respondents in the survey stated emergency medicine, dermatology, geriatrics, neurology and radiology as specialties with telemedicine training in residency. These results were similar to studies published in recent years in the US, including the survey conducted at the Thomas Jefferson University, where 70% of respondents stated integrated telemedicine training in the emergency medicine hospital rotation was valuable to their curriculum, 13 and a national survey of dermatology residents conducted to assess the exposure to teledermatology training and practice indicating the need to expand teledermatology training programs.…”
Section: Discussionmentioning
confidence: 99%
“…The largest study was conducted in France over a 14-year period and reported data for a total of 23,710 patients. 17 The 10 remaining studies reported data for 13,514 patients. 1827 The total cumulative number of patients who received neurosurgical telemedicine consultations captured by this review was 37,224 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…One interesting finding is the breadth of conditions for which teleED was consulted. Prior reports have described single network experiences [26,27] or condition-specific telehealth interventions [28][29][30]. While many networks have developed telehealth infrastructure for cardiac emergencies, trauma, and stroke, that infrastructure is often used for other clinical scenarios where expert consultation may be valued.…”
Section: Plos Onementioning
confidence: 99%